Management of Hypertension in Intrapericardial Paraganglioma - Nicola Rotolo; Andrea Imperatori; Alessandro Bacuzzi; Valentina Conti; Massimo Castiglioni; Lorenzo Dominioni (International Journal of Hypertension)
Functioning paraganglioma is extra-adrenal catecholamine-secreting tumours that may cause secondary hypertension. Primary intrapericardial paragangliomas are very rare and are located adjacent to the great vessels or heart, typically near the left atrium. These tumours are an exceptionally uncommon finding during the investigation of refractory hypertension. However, in recent years, intrapericardial paragangliomas have been diagnosed incidentally with increased frequency, due to the extensive use of radiologic chest imaging. The mainstay of treatment of functioning intrapericardial paraganglioma is surgical removal, which usually achieves blood pressure normalization. Due to the locations of these tumours, the surgical approach is through a median sternotomy or posterolateral thoracotomy, and manipulation-induced catecholamine release may cause paroxysmal hypertension. Typically in these patients, blood pressure fluctuates dramatically intra- and post-operatively, increasing the risk of cardiovascular complications. We review here the current modalities of perioperative fluid and hypotensive drug administration in the setting of surgery for functioning intrapericardial paraganglioma and discuss the recently proposed paradigm shift that omits preoperative preparation.